Gender Effect and the Mediating Role of Work Ethics on the Relationship between Leadership Style and Organizational Culture towards Supply Chain Managerial Efficiency (Study on Yemeni Oil and Gas Industry) - Ibrahim Alkipsy, Ensejam; Raju, Valliappan; Rahman, Shafiqur (ExcelingTech, 2020)
The link between leadership styles and managerial efficiency is well established in literature. However, the role of work ethics, particularly as a mediator, is not well explored in sufficient depth. The objective of this research is therefore to study the effects of both gender, and whether work ethics play a mediating role, on the relationships connecting leadership style, organisational culture and managerial efficiency within the oil and gas industry in Yemen. The study utilised a cross-sectional survey design, sampling 297 middle managers from 13 oil and gas firms in Yemen. Data was collected using a structured questionnaire, and results were analysed statistically using the Partial-Least-Squares technique, utilising Smart-PLS 3. software. Empirical results indicated that leadership styles have both positive and direct effects on managerial efficiency. Furthermore, work ethics were found to significantly mediate the relationships between transactional and participative leadership styles, organisational culture, and managerial efficiency. However, the results also showed that work ethics does not significantly mediate between transformational leadership styles (TRL) and managerial efficiency. The study has implications for top management in the oil and gas industry, offering an opportunity to capitalise on enhancing managerial efficiency by encouraging good leadership styles and management practices that would positively enhance efficiency. Such practices should be made part of the organizational culture, with the goal of creating a harmonious working environment that enables and improves the performance of the firm as a whole.